The Importance of the “Responsibility not to Veto” Debate - Stojkovski, Ljupcho (University of Ljubljana, Faculty of Law, 2017)
The six year war in Syria which has taken over 400.000 lives, led to the displacement of more than 11 million persons and has included war crimes and crimes against humanity, poses a serious challenge for R2P. One of the main reasons for inaction in this conflict is the blockade of the Security Council – as permanent members Russia and China have used their vetoes several times (Russia 6, China 5) to block proposed draft resolutions. The blockade has reinvigorated the appeals for a restrain in the use of the veto by the Permanent Members. This paper examines the Responsibility not to Veto (RN2V) idea – the idea to restraint the veto in the four cases susceptible to R2P. It briefly explores the idea’s history and then focuses on the two latest initiatives – the French proposal and the ACT’s Code of conduct. An analysis of the advantages and disadvantages of these proposals is being conducted, after which an assessment of their chances of success takes place. The paper concludes that similarly to other attempts to reform the UN Security Council, these initiatives do not have a real chance of succeeding any time soon. Nevertheless, the paper offers three reasons why the debate surrounding these proposals is significant and hence should continue. First, the debates indicate an alternative approach in cases when the Security Council is blocked and therefore could improve the issue of right authority for R2P. Second, the wide support that these initiatives enjoy, indicates that the 2005 R2P formula – preparedness for a case-by-case reaction in situations of manifest failure – is not a satisfactory outcome for the international community. Thus, they signal a search for a new understanding of Pillar 3 of R2P. Finally, they show the need for further development and upgrade of ‘R2P-lite’.
Keywords: Responsibility not to Veto (RN2V); UN Security Council (UNSC); Responsibility to Protect (R2P, RToP)